Website-Based Information System for Posyandu Services (Case Study of Posyandu Kemuning 1, Prasung Village) - Danang Firmansyah; Ika Ratna Indra Astutik (Procedia of Engineering and Life Science, 2021)
The development of toddlers is very important to continue to be monitored. Monitoring the growth and development of toddlers is carried out through monthly services at the posyandu, posyandu cadres will record the results of weighing the weight, height, and immunizations that have been received by toddlers. With this system, it is hoped that it can help the implementation process of the posyandu which includes the process of recording the results of the posyandu. This research method uses the System Development Life Cycle (SDLC), which uses a quantitative, systematic, planned, and clearly structured approach from the beginning of the research design. The purpose of this information system is to make it easier for the public to obtain information about the posyandu which includes the results of the posyandu implementation without having to come to the posyandu to ask for data on the results of the posyandu every month. The result of this research is to build a Website-Based Posyandu Service Information System. The conclusion of this study, can be used as an alternative to the use of technology so that it can be used to record the results of posyandu activities and archive storage reports on toddler development quickly, precisely and accurately.